NEW EXPERIMENTAL APPROACH IN BIODOSIMETRY: EX VIVO APOPTOSIS DETECTION - Andrejsová, Lenka; Čížková, Jana; Filipová, Alžběta; Lierová, Anna; Šinkorová, Zuzana (Radiation protection dosimetry, 2022)
This study establishes a new experimental approach for retrospective biodosimetric assessment by apoptosis detection ex vivo. For this purpose, we used mononuclear blood leukocytes isolated from the peripheral blood of irradiated Wistar rats and cultured them ex vivo for posterior analysis. Using flow cytometry, we distinguished apoptotic lymphocyte subsets individual biodosimetric potential at different time periods after exposure: B-lymphocytes 6-8 h (0-7 Gy), natural killer cells 24 h (0-7 Gy) and T-lymphocytes 24 h (0-1 Gy). This novel experimental design innovates through the need of a single blood sample from irradiated individuals for a complete biodosimetric assessment.
Keywords: krysa rodu Rattus; Animals; Rats; apoptóza; retrospektivní studie; Lymphocyte Subsets; zvířata; potkani Wistar; Dose-Response Relationship, Radiation; Flow Cytometry; Rats, Wistar; Retrospective Studies; průtoková cytometrie; vztah dávky záření a odpovědi; Apoptosis; podskupiny lymfocytů